The effect of welding current, arc voltage and welding speed on dimensions of seams cross section - Palić, Vlastimir (Journal of Production Engineering, 1991)
In this paper the influence of variation of welding current, arc voltage and welding speed on dimensions of seams cross section was researched. Experiments were carried out on plates which dimensions are shown on the FIGURE 1. Measured dimensions of seams cross section are shown the FIGURE 2. Welding procedure was submerged arc welding. Welding flux was EP-20, electrode wire was EPP-2 with 5 mm diameter. After welding the plates were broken on the welded joint and dimensions of seams cross section were measured according to FIGU¬RE 2. The one-factor experiment with five levels of factors was applied. In TABLES I and 2 randomization and plan of experiment are shown. In TABLES 3, 4 and 5 measured dimensions of seam are shown, while FIGURES 3, 4 and S represent graph of these dimensions. Basing on measure-Ing results following conclusions are deduct welding current effects most a joint penetration while arc voltage and welding speed most on width of seam.